Effect of wet and dry post-mortem rabbit loin meat ageing on its physicochemical and sensory properties - Aremu, Tolulope Sabainah; Bureš, Daniel; James, Temitope Elizabeth; Lebedová, Nicole; Urbanová, Klára; Dalle Zotte, Antonella; Volek, Zdeněk; Kokošková, Tersia (Meat science, 2025)
Fifty male 90-day-old Hyplus rabbits (PS19 × PS40) were slaughtered (carcass weight: 2126 ± 316.1 g) to determine the effect of post-mortem ageing methods (wet vs dry) and ageing period (7 or 14 days) on the physicochemical characteristics and sensory properties of the longissimus thoracis et lumborum (LTL) muscle. Of the 50 carcasses, 10 were used for physicochemical meat quality assessment on 24 h post-mortem (D1). The remaining carcasses were assigned to either wet ageing (deboned muscles in vacuum-packaging) or dry ageing (whole carcass), for 7 "D7" or 14 "D14" days (n = 10 per treatment combination). Physicochemical and sensory analyses were performed after each ageing period. Results revealed that wet-aged LTLs were lighter in colour (L*) than the dry-aged LTLs, regardless of the ageing period. The wet-aged samples also had the highest a* values (redness) on D14 than all other treatments. Cooking loss percentages were greater in wet- than dry-aged meat on D14, but did not differ on D1 and D7 of wet ageing. Shear force decreased from D1 to D7 of ageing, regardless of the method used, and then stabilised. The dry-aged meat on D14 exhibited the lowest moisture content and the highest ash content, whilst the greatest malondialdehyde concentration was reported on D7 for dry-aged meat corresponding with its higher scores for off-odour intensity by the sensory panel. Whilst no significant differences were noted for overall acceptance on D7, the positive flavour development during dry ageing after 14 days was favourably evaluated by the panellists.
Keywords: Animals; kosterní svaly; Cooking loss; Rabbits; Cooking; Flavour; Off-odour; barva; lidé; maso; Meat; Food Handling; Color; posmrtné změny; chuť; Muscle, Skeletal; voda; manipulace s potravinami; Water; Male; Malondialdehyde; Vacuum packaging; Taste; Postmortem Changes; králíci; mužské pohlaví; zvířata; vaření; Humans